Catalyzing a regional bond market - Raman, F. Venkat ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Discusses the place of bond markets in any modern economy, the role of credit ratings in developing bond markets and the appropriateness of regional capital markets for the Caribbean. Explains the contribution that the Caribbean Information & Credit Rating Services Limited (CariCRIS) can make towards developing a vibrant regional debt market in the Caribbean.